If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3m + 2 = 0 Reorder the terms: 2 + -3m = 0 Solving 2 + -3m = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -3m = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -3m = 0 + -2 -3m = 0 + -2 Combine like terms: 0 + -2 = -2 -3m = -2 Divide each side by '-3'. m = 0.6666666667 Simplifying m = 0.6666666667
| 8x^2+5x+11=0 | | f(x)=-2x^2-20x-54 | | 5x+6-10x=-39 | | x+3/4=9/2 | | 2-x=40 | | .5x+x=490.5 | | 2-x=48 | | C(q)=25q+40000 | | 10+8p=8(1-5p)+2 | | 2+x=40 | | 12x+4y=450 | | x^2-2x=x+5 | | 9e+r=14+8e | | 2k+7k=25k | | 35=7m+49 | | x^2-3x=x-7 | | 4n^3+6n^2+4n=0 | | 8x+1=7x+2 | | 100-4d=0 | | 1900+x=51100 | | 3(2x-5)-4=33 | | log(3x-4)=-0.1 | | 2xy+y=7 | | 5(2x+2)=9x+3 | | 6.3=2x-(-4.5) | | 4(2x-5)=-2(1-x) | | 9XY^2-6Y^3=0 | | 3b^2+3=0 | | 100-4d=40 | | 700+0.2x=1800 | | -3+15=4b-8-3b | | Y=1.14x+6 |